Implementasi Pembelajaran Berbasis Masalah untuk Meningkatkan Prestasi Belajar Siswa - Suriswo suriswo; Manfur manfur (Cakrawala: Jurnal Pendidikan, 2019)
The aim of this research is to develop a learning model that can improve student achievement. Analyzing the effectiveness of the problem-based learning model (PBM) can improve student achievement higher than the previous learning outcomes that do not use PBL learning models in SD Negeri Kagok 01 Slawi District, Tegal Regency. Knowing the form of support from the principal, other teachers and facilities in the implementation of the PBM learning model. The target of this research is expected to find empirical data and facts is the desired product of this research and development in the form of PBM learning models. The research method will be implemented namely Field Prasurvey (factual model), collecting data relating to: (a) students; (b) teaching and learning process; (c) teacher and (d) facilities and environment. The draft model (a) design of the model, consists of formulating competencies, determining material, and preparing lesson plans, determining methods, media, and evaluation; (b) Application of the model by conducting a pre test. (c). Application of the model by conducting a post test. (d). Conduct analysis by comparing pre test and post test scores with t tests. From the results of calculations with the t test obtained, the empirical t test is greater than the t test in the table, so it is concluded that the PBM model is more effective.